2008
DOI: 10.1016/j.jacc.2007.10.067
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Valve Replacement for Low-Flow/Low-Gradient Aortic Stenosis

Abstract: In view of the very poor prognosis of unoperated patients, the current operative risk, and the long-term outcome after surgery, AVR is the treatment of choice in the majority of cases of LF/LGAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(54 citation statements)
references
References 22 publications
4
42
0
1
Order By: Relevance
“…This phenotype is often misleading for clinicians because establishing the diagnosis can be challenging and the prognosis falsely reassuring given a heart that is not dilated or hypokinetic (to the contrary, the LV often appears hyperdynamic). However, studies have convincingly shown, and our data reaffirm, that paradoxical low‐gradient AS constitutes a particularly high‐risk group with operative risk of 6% to 33% and medically treated survival <50% at 3 years 27, 28, 29, 30. Patients with paradoxical low‐gradient AS are particularly vulnerable to the deleterious effects of patient‐prosthesis mismatch and, accordingly, may be good candidates for TAVR.…”
Section: Discussionsupporting
confidence: 75%
“…This phenotype is often misleading for clinicians because establishing the diagnosis can be challenging and the prognosis falsely reassuring given a heart that is not dilated or hypokinetic (to the contrary, the LV often appears hyperdynamic). However, studies have convincingly shown, and our data reaffirm, that paradoxical low‐gradient AS constitutes a particularly high‐risk group with operative risk of 6% to 33% and medically treated survival <50% at 3 years 27, 28, 29, 30. Patients with paradoxical low‐gradient AS are particularly vulnerable to the deleterious effects of patient‐prosthesis mismatch and, accordingly, may be good candidates for TAVR.…”
Section: Discussionsupporting
confidence: 75%
“…23 Nonrandomized data suggest that regardless of the origin, patients with LF AS with LG have worse outcomes with and without surgery yet may still benefit from valve replacement compared with MM. 6,[8][9][10][11][12][13][14] In our analysis of patients with severe AS and predominantly not LGs, a low stroke volume was an important independent predictor of midterm all-cause mortality compared with patients with NF. Although current guidelines emphasize the importance of EF in the evaluation of patients with AS for surgery even when asymptomatic, our data suggest that EF may be less important after adjustment for flow.…”
Section: Pathophysiology Of Lfmentioning
confidence: 59%
“…[3][4][5][6][7] These patients have a prognosis similar to or worse than that for patients with classic AS, both with and without surgery. [6][7][8][9][10][11][12][13][14] However, little is known about the prognostic value of LF independently of gradient and EF and its treatment.…”
mentioning
confidence: 99%
“…According to recent studies, patients with left ventricular contractile reserve (CR) on DSE (i.e., an increase in stroke volume under dobutamine infusion of Ն20% compared with the baseline value) have a relatively low operative mortality, about 5% to 7% (2,3). Therefore, patients with severe LF/LGAS and CR have an acceptable operative risk, and aortic valve replacement (AVR) improves long-term survival and functional status in most cases (2)(3)(4).…”
Section: Discussionmentioning
confidence: 99%